Emission spectroscopy of transversal atmospheric pressure discharges - Prysiazhnevych, I.V.; Chernyak, V.Ya.; Yukhymenko, V.V.; Olshewskii, S.V.; Lisitchenko, T.E. (Вопросы атомной науки и техники, 2009)
Plasma properties of the transversal discharges (transverse arc and the discharge in gas channel with liquid wall) were investigated by optical emission spectroscopy. Population distribution temperatures of excited states of atoms and molecules in generated plasmas were determined. Relative concentrations of radiating plasma components were estimated by using method suggested in this work. The comparative analysis of plasma parameters of different transversal atmospheric pressure discharges was made. Методом оптичної емісійної спектроскопії досліджено властивості плазми поперечних розрядів (поперечної дуги та розряду в газовому каналі з рідкою стінкою). Визначені температури заселення збуджених рівнів атомів та молекул у генерованих плазмах. За допомогою запропонованого в даній роботі методу оцінені відносні концентрації випромінюючих компонентів плазми досліджених розрядів. Проведено порівняльний аналіз параметрів плазми різних поперечних розрядів атмосферного тиску. Методом оптической эмиссионной спектроскопии исследованы свойства плазмы поперечных разрядов (поперечной дуги и разряда в газовом канале с жидкой стенкой). Oпределены температуры заселения возбужденных уровней атомов и молекул в генерированных плазмах. С помощью предложенного в данной работе метода оценены относительные концентрации излучающих компонент плазмы исследуемых разрядов. Проведен сравнительный анализ параметров плазмы различных поперечных разрядов атмосферного давления.